METHODOLOGY FOR DEVELOPING SCHOOLCHILDREN’S AESTHETIC TASTE AND VISUAL THINKING THROUGH VISUAL ARTS - Usmonova Ruxshona Feruz qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the methodology for developing schoolchildren’s aesthetic taste and visual thinking through visual arts lessons. The study examines effective pedagogical strategies that enhance students’ artistic perception, creativity, and critical thinking. It emphasizes the role of visual arts in cultivating an appreciation for beauty, understanding of forms and colors, and the ability to interpret and express ideas visually. Practical recommendations are provided for lesson planning, implementation, and the integration of interactive and hands-on activities to foster students’ aesthetic and cognitive development.